FEATURES OF THE PSYCHOLOGICAL STATE IN PREPARATION FOR SPORTS COMPETITIONS - Masimjonov , Azizjan Adiljan o‘g‘li (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
Strengthening and maintaining the health of the younger generation is one of the top priorities of the state’s national policy, as currently designated by the president. This task is meant to be accomplished by putting into action a plan to construct new sports facilities that adhere to international standards and by encouraging more kids and teenagers to participate in sports, with an emphasis on extending the sphere of influence of physical culture and sports to the issue of educating a healthy lifestyle. We can talk about the characteristics of competitors’ psychological states as they get ready for competition in this article.